POLICIES, CHALLENGES AND STRATEGIES FOR MUNICIPAL WASTE MANAGEMENT IN MALAYSIA (Journal of Science, Technology and Innovation Policy, 2021)
Municipal waste management (MWM) in Malaysia has become a challenging task in recent years due to population growth, industrialisation and an increase in quantity and variation in the types of waste generated. Suitable disposal sites are becoming scarce and most of the existing ones are nearly coming towards the end of its useful life. The government has promoted recycling programmes through various campaigns however little has been achieved due to the lack of participation and lukewarm attitudes of the public in Malaysia. Therefore, this paper is written to provide an overview and analysis of the policies, challenges and strategies to issues related to MWM in Malaysia.
Keywords: Municipal waste management, environmental management, technology management, Malaysia